Nonalcoholic Fatty Liver Disease versus Alcohol-related Liver Disease: Is it Really so Different? - Craciun, Ana; Lackner, Caroline; Cortez-Pinto, Helena (Current Pharmaceutical Design, 2020)
Nonalcoholic fatty liver disease and alcohol-related liver disease together, compose the majority of cases of liver disease and cirrhosis worldwide. Although in the last years, there has been much interest in the differentiation between the two entities, it is increasingly recognized that a large overlap exists between them. The main pathophysiological aspects are very similar, with the exceptions of mechanisms directly related to alcohol, acting as an added factor in the presence of metabolic risk factors. Genetic factors so far identified are also very similar. In both cases, the disease is more prevalent in males, the difference being more significant in the ALD group, having to do with harmful alcohol consumption, which is more frequent in males. NAFLD advanced stages usually present in older age than ALD. Regarding laboratory features, the ratio AST/ALT < 1 is more frequent in NAFLD than ALD, in the absence of cirrhosis. Histological aspects of both situations are very similar, but some are specific for ALD, such as alcoholic foamy degeneration or cholestasis, or fibroobliterative venous lesions. Regarding treatment, several drugs now included in clinical trials in NAFLD, could also be assayed in ALD, since similar mechanisms of action, are potentially acting in ALD. In summary, similarities seem to outnumber differences, and since so large overlap between risk factors exist, the use of a common designation such as Fatty Liver Disease (FLD) or Metabolic Fatty Liver disease (MEFLD), could better serve the field.
Keywords: alcohol